The Conceptualization of an Innovative Business Model - the Case of a Technology Enterprise - Ewa Badzinska (Institute of Economic Research (IER), 2017)
The complexity and dynamic changes of external conditions necessary for enterprises to function and increased competition in the local and global markets impose constant search for the most effective business model for the development of organizations. Its accurate identification and measurement influence the utilization of internal capacity of organizations, market opportunities and application of adequate instruments of competition. The scientific purpose of the study is to conduct a creative synthesis of the theoretical framework concerning business models. The empirical part of the paper is an attempt to present the conceptualization and descriptions of a real business model. It has been developed by young Polish IT enterprise for the implementation of a service for creating modern technological-programming solutions on the international market. The paper is of analytical and conceptual character. The application of the empirical method of a case study has made it possible to characterize the essence of creating an innovative business model and illustrate the progress of the studied phenomenon in business practice. The exploratory research has been conducted with regard to technological solutions offered by MindsEater Ltd. The research results reveal the existence of interdependencies between intellectual potential of staff members and success in business practice. By creating and implementing innovative business model, the enterprise must take into account the context of micro-business as well as social, economic and political environment in which it operates and the goals and mission of its activity. The conducted research is an authorial attempt to explain the concept of an innovative business model.
Keywords: O21; O31; O32; O33; 330; business models; entrepreneurship; intellectual potential; sustainability; technological solutions